FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM PEMBELIAN PRODUK COKELAT NDALEM DI CV NDALEM MULYA MANDIRI YOGYAKARTA - Fatna Trihastuti Anjani; Indah Widowati; Budiarto Budiarto (Jurnal Dinamika Sosial Ekonomi, 2018)
This research aims to analyze the influence of cultural, social, personal and psychological factors towords consumer behavior in purchasing nDalem chocolate products in CV nDalem Mulya Mandiri. The method used in this research is descriptive method, while the implementation is conducied through a case study, and the method used to choose the consumer is non probability sampling. The analytical technique used in this research is multiple linier regression analysis. The result of the research shows that the cultural, social, personal and psychological factors affect consumer behavior in purchasing nDalem chpcplate products in CV nDalem Mulya Mandiri Yogyakarta. Keywords: nDalem chocolate products, cultural, social, personal, psychological factors, consumer nehavior.